Table of Content - - (Journal of Humanities & Social Sciences, 2023)
Table of Content1. Family reform and its link to solving the problems facing working women and their multiple roles: Applied study on a sample of women working in the private sector in JeddahMr. Samir Khalaf Atiq Al-Mutairi2. Symbol Aesthetics in Mesopotamia PotteryMr. Omar Mohmmad Samer Abdui-Hafedh, Prof. Hamideh Jafari3. The Effectiveness of a Proposed Educational Unit for Training on the Wilcom Program in Machine Embroidery Technology CourseMrs. Amani Abdu Ahmad Alzayla'aee, Co-Prof. Kherah Award Alzahrani4. Palestinian Scientific Research from the Perspective of Bachelor's Students: Exploring Reality and AspirationsDr. Osama Issam Matar , Dr. Reem Mashhour Jawabreh , Mrs. Haya Yaser Radwan, Dr. Mohammad Shareef Ayyash, Mr. Thaher Mohamed Gharabeh, Mr. Abedelrahman Aqel Alhajhamad1, Dr. Ashraf Mohammed Abualrob, Mrs. Aseel Adly Halabi, Mr. Diya Mohammed Abu Shomer, Mrs. Sherin Wael Kaleef5. Negative manifestations on occasion of joys and their impact on Saudi society: A study applied to Afif governorateMr. Talal Fahd Munir Al-Otaibi6. Personal Data Protection in the Kingdom of Saudi Arabia, EU and UK GDPR: A Comparative StudyMr. Najim Abdullah Al-Shammari7. Evaluation of service area and ease of access to public hospitals in Riyadh using GISMr. Sahoud Rahim Al-Adhyani8. The Role of Social Work in Facing the Negative Effects of Cyberbullying on Adolescents  in Saudi ArabiaMrs. Meaad Shahad Zayed Al-Sulami
Keywords: Journal of Human And Social Sciences